Slow gut transit increases the risk of Alzheimer’s disease: An integrated study of the bi-national cohort in South Korea and Japan and Alzheimer’s disease model mice - Jiseung Kang; Myeongcheol Lee; Mincheol Park; Jibeom Lee; Sunjae Lee; Jaeyu Park; Ai Koyanagi; Lee Smith; Christa J. Nehs; Dong Keon Yon; Tae Kim (Journal of Advanced Research)
Introduction: Although the association between Alzheimer's disease (AD) and constipation is controversial, its causality and underlying mechanisms remain unknown. Objectives: To investigate the potential association between slow gut transit and AD using epidemiological data and a murine model. Methods: We conducted a bi-national cohort study in South Korea (discovery cohort, N=3,130,193) and Japan (validation cohort, N=4,379,285) during the pre-observation period to determine the previous diagnostic history (2009–2010) and the follow-up period (2011–2021). To evaluate the causality, we induced slow gut transit using loperamide in 5xFAD transgenic mice. Changes in amyloid-beta (Aβ) and other markers were examined using ELISA, qRT-PCR, RNA-seq, and behavioral tests. Results: Constipation was associated with an increased risk of AD in the discovery cohort (hazard ratio, 2.04; 95% confidence interval [CI], 2.01–2.07) and the validation cohort (hazard ratio; 2.82; 95% CI, 2.61–3.05). We found that loperamide induced slower gut transit in 5xFAD mice, increased Aβ and microglia levels in the brain, increased transcription of genes related to norepinephrine secretion and immune responses, and decreased the transcription of defense against bacteria in the colonic tissue. Conclusion: Impaired gut transit may contribute to AD pathogenesis via the gut-brain axis, thus suggesting a cyclical relationship between intestinal barrier disruption and Aβ accumulation in the brain. We propose that gut transit or motility may be a modifiable lifestyle factor in the prevention of AD, and further clinical investigations are warranted.